2014
DOI: 10.24199/j.mmv.2014.71.05
|View full text |Cite
|
Sign up to set email alerts
|

Morphological anomalies in polychaetes: Perinereis species (Polychaeta: Annelida) examples from the Brazilian coast

Abstract: The examination of a large number of specimens in the context of taxonomic and ecological studies may lead to the discovery of morphological anomalies. The aim of this study was to describe the morphological anomalies observed in some individuals of Perinereis anderssoni and Perinereis ponteni collected in various regions of the Brazilian coast. A total of 290 specimens were analysed from along the northern and southern Brazilian coast, and 21 of these presented morphological anomalies, such as variations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…According to Ten Hove and Eliahu (2005), this state concerns a transient and very short ontogenetic state due to a guarantee of the reproduction and, therefore, the continuity of life in environments with high contamination. Previous studies reported that malformations or anomalies in polychaetes were related to exposure to pollutants and its effects at many levels: individual, specific, population, and community (Coutinho and Santos, 2014). More recent studies on samples collected elsewhere have shown that when two opercula are present, the largest operculum directly or indirectly inhibits the developmental power of the smallest, leading to a state of equilibrium (Kubal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to Ten Hove and Eliahu (2005), this state concerns a transient and very short ontogenetic state due to a guarantee of the reproduction and, therefore, the continuity of life in environments with high contamination. Previous studies reported that malformations or anomalies in polychaetes were related to exposure to pollutants and its effects at many levels: individual, specific, population, and community (Coutinho and Santos, 2014). More recent studies on samples collected elsewhere have shown that when two opercula are present, the largest operculum directly or indirectly inhibits the developmental power of the smallest, leading to a state of equilibrium (Kubal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Perinereis spp. and Alitta succinea can be easily found in shallow waters (Coutinho and Santos, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Michel, 1909; Stephan‐Dubois & Bautz, 1969; Ribeiro & Aguado, 2021), or supernumerary or infranumerary structures (e.g. Prentis, 1901; Herpin, 1914a; Rasmussen, 1973; Creaser & Bean, 1990; Bastida‐Zavala & ten Hove, 2002; Çinar & Ergen, 2005; Coutinho & Santos, 2014; Ribeiro et al ., 2020).…”
Section: Bifurcated Annelidsmentioning
confidence: 99%